Vocabulary Learning Strategies Used by Class Ten Students - Tiwari, Hari Prasad (Nepal Journal of Multidisciplinary Research, 2023)
Learning vocabulary is a key component of communication and comprehension. Students need to use effective Vocabulary Learning Strategies (VLS) to learn and retain new words and expand their word knowledge. This quantitative study used a descriptive survey research design to find out the VLS of class ten students. The participants consisted of 30 class ten students who were sampled using stratified sampling method. The data was collected employing structured questionnaire which included 30 rating scale questions. The data was analyzed using descriptive statistics and frequency counts to identify the most and least used strategies. The findings revealed that the students used a range of strategies, but some were more dominant than others. One of the most common cognitive strategies was guessing the meaning of unknown words from context, indicating that the students relied on their prior knowledge and reading skills. Similarly, one of the most popular social strategies was asking for clarification from teachers or peers, suggesting that the students valued the role of interaction and feedback in vocabulary learning. These results demonstrated that the students were flexible and resourceful in their strategy use and could adapt to different vocabulary learning tasks and goals. The study has some limitations, such as the limited sample size and the potential inaccuracies in self-reported data. Therefore, further research with larger and more representative samples is recommended. Despite these limitations, this study contributed to the understanding of VLS among class ten students in Nepal and offered implications for vocabulary teaching and learning.